Low band gap benzimidazole COF supported Ni3N as highly active OER catalyst - Nandi, Shyamapada; Singh, Santosh Kumar; Mullangi, Dinesh; Illathvalappil, Rajith; George, Leena; Vinod, Chathakudath P.; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2016)
Covalent organic frameworks (COFs) have structures and morphologies closely resembling graphenes, whose modular construction permits atomiclevel manipulations. This, combined with their porous structure, makes them excellent catalyst supports. Here, the high electrocatalytic activity of a composite, formed by supporting Ni3N nanoparticles on a benzimidazole COF, for oxygen evolution reaction is shown. The composite oxidizes alkaline water with a near-record low overpotential of 230 mV @ 10 mA cm(-2) (eta(10)). This high activity is attributed to the ability of the COF to confine the Ni3N nanoparticles to size regimes otherwise difficult to obtain and to its low band gap character (1.49 eV) arising from the synergy between the conducting Ni3N nanoparticles and the pi-conjugated COF. The COF itself, as a metalfree self-standing framework, has an oxygen evolution reaction activity with 10 of 400 mV. The periodic structure of the COF makes it serve as a matrix to disperse the catalytically active Ni3N nanoparticles favoring their high accessibility and thereby good charge-transport within the composite. This is evident from the amount of O-2 evolved (230 mmol h(-1) g(-1)), which, to the best of our knowledge, is the highest reported. The work reveals the emergence of COF as supports for electrocatalysts.

High-level supercapacitive performance of chemically reduced graphene oxide - Jha, Plawan Kumar; Singh, Santosh Kumar; Kumar, Vikash; Rana, Shammi; Kurungot, Sreekumar; Ballav, Nirmalya (Chem, 2017)
Reduction of graphene oxide (GO) is an important process because it holds promise for the production of reduced graphene oxide (rGO) with physicochemical properties similar to those of pristine graphene. In conventional chemical reduction, strong reducing agents, such as sodium borohydride and hydrazine, cannot be recycled. Also, fast reaction kinetics bring an imbalance in the desirable properties of rGO. Here, we present one-pot chemical reduction of GO in aqueous medium by an unconventional mild reducing agent (FeCl2/HCl) where rGOis isolated as the precipitate and the reducing agent is recycled upon simple treatment of the filtrate with HCl. The fabricated all-solid-state supercapacitors of as-synthesized rGO exhibited significantly higher specific capacitance than those obtained with rGO derived from conventional reducing agents. The cycling stability of the all-solid-state supercapacitor (> 80% retention of capacitance beyond 100,000 continued cycles) and its flexibility (> 500 bending cycles) were remarkable. Use of commercially available organic electrolyte further boosted the supercapacitor performance.